Effects of career guidance, internship experience, emotional intelligence, and soft skills on students’ work readiness - Reno Fitlova Chaspi; Usmeldi Usmeldi; Dedy Irfan; M. Giatman (Global Econedu, 2026)
This study aimed to examine the effects of career guidance, internship experience, emotional intelligence, and soft skills on the work readiness of students at SMKN 7 Sijunjung. This study employed a quantitative correlational design involving 73 twelfth-grade students selected using purposive sampling. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics, assumption tests, simple and multiple regression analyses, t-tests, F-tests, and coefficients of determination. The results revealed that career guidance, internship experience, emotional intelligence, and soft skills each had positive and significant effects on work readiness, contributing 21.6%, 35.3%, 20.2%, and 24.7%, respectively. Simultaneously, these variables explained 46.2% of the variance in work readiness. These findings indicate that strengthening educational support and personal competencies is essential for enhancing vocational students' readiness for employment.